The impact of continuous training in small and medium enterprises: Lessons from an industrial case analysis - Pérez-Bustamante Ilander, Guillermo O.; Marques, Carla S. E.; S. Jalali, Marjan; A. F. Ferreira, Fernando (Journal of Business Economics and Management, 2016)
In the current competitive environment, great emphasis is placed on the knowl- edge and skills of the workforce as important elements in achieving organizational goals. As this focus on employee skills has increased, so have organizational programs and initiatives to ensure that the training in place to develop those skills is not sporadic, but rather part of a continuous effort toward keeping employee skills up to date. It becomes fundamental, in this context, to understand such programs and evaluate their impact, both within companies and externally, in terms of their decision making and business results. This paper aims to do that, through a study of the work-related training practices of in- dustrial firms in the Northern-Spanish region of Asturias. In addition, it develops a new variable – training intensity – and examines its impact on the planning, execution and evaluation of training programs in these firms. Among other findings, our study confirms that training-intensive firms have a more defined strategic approach to the market and are generally more conscious of business competition than their non-training-intensive competitors. Implications for management are also presented.